Effects of a recreational therapy program on the depressive state of elderly institutionalized in El Cottolengo, 1988-1989 (Colombia Medica, 1993)
This study done with institutionalized elderly in Cottolengo, Jamundí, had a quasi-experimental design and the following hypothesis: "The elderly who attend recreation therapy lessen their depression state." The socio-demographic characteristics and health status of the 73 subjects in the initial sample were as follows: mean age, 75 years without statistically significant difference by sex; most were single; the previous occupation was related to the low educational level. Sixty-three percent did not feel well, 24% had respiratory complains, and 8.2 % had osteomuscularcomplains.Thirty elderly who attended 63.8% of the recreation therapy meetings were assessed for depression state before and after the recreation therapy. The multiple regression analysis showed a statistically significant difference (t= 4.49, > p= 0.00), thus accepting the hypothesis related to the decrease in the depression state among the elderly who attended recreation therapy. It is concluded that recreation therapy contributes to maintaining the physical and mental health status of the institutionalized elderly.